A new genus and new species of metalmark moths (Lepidoptera: Choreutidae) from Costa Rica - Rota, Jadranka (Zootaxa, 2008)
Alasea, new genus, is described and illustrated. As currently defined, Alasea is monotypic with the single species A. corniculata, n. sp., from Heredia, Limón, and Puntarenas provinces in Costa Rica. The new genus is assigned to the subfamily Choreutinae based on morphological and molecular data. As in other choreutines, Alasea has a bluntly pointed forewing and hindwing (in Brenthiinae the wings are obtuse); the basal segment of the labial palpus is parallel-sided (in Brenthiinae it is narrowed basally); and the basal flagellomeres of the antenna are heavily scaled (in Brenthiinae such scaling is never present). The immature stages and the biology of A. corniculata are unknown. Additionally, the terminology and homology of genitalic characters used in descriptions of Choreutidae are reviewed, and suggestions for more consistent usage are provided.